The lung rescue unit—Does a dedicated intensive care unit for venovenous extracorporeal membrane oxygenation improve survival to discharge?. Issue 3 (September 2017) - Menaker, Jay; Dolly, Katelyn; Rector, Raymond; Kufera, Joseph; Lee, Eugenia E.; Tabatabai, Ali; Rabinowitz, Ronald P.; Kon, Zachary N.; Sanchez, Pablo; Pham, Si; Herr, Daniel L.; O'Connor, James V.; et al.
Abstract : BACKGROUND: The use of venovenous extra corporeal membrane oxygenation (VV ECMO) for acute respiratory failure (ARF)/acute respiratory (ARDS) has increased since 2009. Specialized units for patients requiring VV ECMO are not standard and patients are often cohorted with other critically ill patients. The purpose of this study was to report the outcome of adult patients admitted in 2015 to the lung rescue unit, which, to our knowledge, is the first intensive care unit in the United States that has been specifically created to provide care for patients requiring VV ECMO. METHODS: Data were collected on all patients admitted to the lung rescue unit on VV ECMO between January 1, 2015, and December 31, 2015. Demographics, medical history, pre-ECMO data, indication for VV ECMO as well as duration of ECMO and survival to decannulation and discharge were recorded. Means (± standard deviation) and medians (interquartile range [IQR]) were reported when appropriate. RESULTS: Forty-nine patients were enrolled. Median age was 48 years (IQR, 32–57). Median PaO2 /FIO2 ratio before cannulation was 66 (IQR, 53–86). Median ventilator days before cannulation was 2 (IQR, 1–4). Median time on VV ECMO for all patients was 311 hours (IQR, 203–461). Thirty-eight (78%) patients were successfully decannulated with 35 (71%) patients surviving to hospital discharge. CONCLUSION: The use of VV ECMO for ARF/ARDS is increasing. We have demonstrated that a dedicated multidisciplinary intensive care unit for the purpose of providing standardized care with specialized trained providers can improve survival to discharge for patients that require VV ECMO for ARF/ARDS. LEVEL OF EVIDENCE: Therapeutic, level V.